2012
DOI: 10.5114/pg.2012.29881
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in patients with decompensated liver cirrhosis – a pilot study

Abstract: Introduction: Cirrhosis is associated with many disorders of the cardiovascular system defined "cirrhotic cardiomyopathy". They concern, among others autonomic imbalance. One of the ways to evaluate these disorders is to study the heart rate variability (HRV). Abnormal HRV values occur in hypertension, ischemic heart disease, post myocardial infarction and heart failure. Are one of the prognostic factors. Aim: Evaluation of parameters of HRV in 24-hour Holter monitoring in patients with decompensated cirrhosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
2
4
0
1
Order By: Relevance
“…Disorders of diurnal variation HRV are typical of many diseases including diabetes and diabetic neuropathy, 38 alcoholic neuropathy 39 or liver cirrhosis. 29 In our study, we confirmed the change in HRV parameters depending on the time of day in the control group of healthy people. In daytime, the values of corresponding sympathetic activity were significantly higher, including SDANN and TrI, and in night resting hours – parasympathetic – r-MSSD, p50NN and HF band.…”
Section: Discussionsupporting
confidence: 81%
“…Disorders of diurnal variation HRV are typical of many diseases including diabetes and diabetic neuropathy, 38 alcoholic neuropathy 39 or liver cirrhosis. 29 In our study, we confirmed the change in HRV parameters depending on the time of day in the control group of healthy people. In daytime, the values of corresponding sympathetic activity were significantly higher, including SDANN and TrI, and in night resting hours – parasympathetic – r-MSSD, p50NN and HF band.…”
Section: Discussionsupporting
confidence: 81%
“…It is in line with our earlier studies. In those studies, we demonstrated a similar profile of autonomic disorders in patients with cirrhosis decompensation [ 40 ]. The parasympathetic system characterising parameters were also significantly lower in that particular case.…”
Section: Discussionsupporting
confidence: 56%
“…Cirrhosis induces hemodynamic disturbances, peripheral nerve disorders, electromechanical conjunction, and dysfunction in the autonomic nervous system (ANS), and these occur independently of the etiology [12]. The liver is innervated with many branches of the ANS.…”
Section: Introductionmentioning
confidence: 99%
“…Primary Biliary Cholangitis (PBC) is associated with other pathologies, and is known as cirrhotic cardiomyopathy when it is associated with cardiovascular disturbances. A decreased HRV is correlated with cirrhosis and vascular changes [12]. There is evidence showing the myocardial repolarization lability is significantly altered in end-stage liver disease [21].…”
Section: Introductionmentioning
confidence: 99%